افعال ملعون فاعلھا - Naseer Ahmed Akhtar; Samiya ALLAH Ditta (The Islamic Culture, 2018)
Every wise person knows that every action (Amal) has result (consequences), and these consequences appear after action. If the consequences are useful for the performer, he gets happy and successful. If the consequences are not in favour, he/she becomes sad. Now he can not do anvthing because the work has already taken place, and there is no other option except, accept the result. Therefore, the loser blames himself. Guilty feeling can not undo the lose. Everyone wishes to do productive work and stay _ away from bad works, therefore, it is mandatory for evervone to understand what is good for him and what is harmful so that he can get success and take advantage of blessing in this world and hereafter.If we keenly observe, human is the only creature whose actions (Amal) improve. God has inculcated this thought in human so that all the time they can understand with the help of these two things.(i) using his senses for understanding (ii) Following Divine books which were give to phrophes, and which teach Allah's love and fear.